Determination of KD025 (SLx-2119), a Selective ROCK2 Inhibitor, in Rat Plasma by High-Performance Liquid Chromatography-Tandem Mass Spectrometry and Its Pharmacokinetic Application - Jin-Ha Yoon; Thi-Thao-Linh Nguyen; Van-An Duong; Kwang-Hoon Chun; Han-Joo Maeng (Molecules, 2020)
KD025 (SLx-2119), the first specific Rho-associated protein kinase 2 (ROCK2) inhibitor, is a potential new drug candidate currently undergoing several phase 2 clinical trials for psoriasis, idiopathic pulmonary fibrosis, chronic graft-versus-host disease, and systemic sclerosis. In this study, a bio-analytical method was developed and fully validated for the quantification of KD025 in rat plasma and for application in pharmacokinetic studies. KD025 and GSK429286A (the internal standard) in rat plasma samples were analyzed by high-performance liquid chromatography-tandem mass spectrometry with m/z transition values of 453.10 → 366.10 and 433.00 → 178.00, respectively. The method was fully validated according to the United State Food and Drug Administration guidelines in terms of selectivity, linearity, accuracy, precision, sensitivity, matrix effects, extraction recovery, and stability. The method enabled the quantification of KD025 levels in rat plasma following oral administration of 5 mg/kg KD025 and intravenous administration of 2 mg/kg KD025 to rats, respectively. Our findings suggest that the developed method is practical and reliable for pharmacokinetic studies of KD025 in preclinical animals.